THE HISTORICAL-LOCAL HERITAGE AS AN EFFECTIVE MECHANISM OF ETHNODIZING EDUCATION - Гаврилюк, Р. М. (Art and Design, 2020)
The dissemination of the local lore and the strengthening of the educational and methodological base of local lore in the system of ethno-design education, the popularization of the historical-lore heritage of the Vyzhnytsia art center, the actualization of methodological foundations of ethno-design teaching, their scientific substantiation of importantance. Methodology. The article uses general scientific methods of descriptive, comparative, the method of systematization and synthesis. During the studing of local lore the analytical method of research, as well as the methods of classification of components of professional competencies in ethno-design education of future specialists of creative direction, were used, which will contribute to the direct realization of perspective projects of the graduates of Vyzhnytsia Applied College of Arts and Design named after Vasil Shkribliak in the creativity and the cultural field of Ukraine. Results. As a result of the research it is established ,that the historical and local lore is the basis of creative activity in various fields of art and design. It is determined, that the processes of globalization, characteristic of modern society, require the understanding of the problems of the national revival, the reflection of the manifestation of the national culture features in modern ethno-design. The ethno design methodology is becoming an important component of modern culture and leads to significant changes in the composition of the aesthetic characteristics of the subject environment. The inclusion of the components of the national culture and ethno-design in the educational process gives the opportunity to form the creative professional thinking of future graduates of Vyzhnytsia Applied College of Arts and Design named after Vasil Shkribliak. Scientific novelty. The idea of forming the scientific basis for exploring the perspectives of conceptual transformations of ethno-design in Ukraine, taking into account the processes of globalization and regional specificity, was further developed in the article; the understanding of the influence of socio-political situation in Ukraine on the development of ethno-design. Practical significance. The main statements of the article can be the theoretical, factual and historiographic basis for the development of general and special lecture courses and seminars at the educational establishments of arts and culture, as well as used in the educational process for preparatory courses in ethno-design.